Accidental Penetrating Thoracic Injury with a Screwdriver in a Child: A Case Report - Usha Kumari; Fakhar Abbas; Zara Shirazi; Nosheen Hafeez; Sohail Bangash (Journal of Tehran University Heart Center, 2022)
Accidental penetrating injuries are common among children, either with a sharp or a blunt object. The screwdriver is an uncommon weapon; therefore, injuries caused by it represent an even rarer subset. Inadvertent injuries in the chest with a screwdriver as a stabbing weapon are extremely unusual. Penetrating chest injuries can be fatal if they cause wounds in the cardiac chambers or major thoracic vessels. We describe a 9-year-old child with an unintentional penetrating thoracic injury caused by a screwdriver. An explorative left anterior thoracotomy showed that the tip of the implanted screwdriver was lying near the left subclavian vessels and the apex of the lung, but it did not perforate any of those. The screwdriver was dislodged, and the wound was closed. The patient had an event-free 1-week hospital stay.